Tense And Aspect In Akan Serial Verb Constructions - Owusu, Augustina (My University, 2022)
In Akan, tense and aspect in serial verb constructions have different distributions. Tense is repeated on all the verbs; aspect only appears on the first verb, the following verbs have the à marker. In this paper, I argue that this difference in distribution is a consequence of being evaluated by different syntactic mechanisms. Evaluation of unvalued features is licensed by two syntactic mechanisms, Agree and Selection/Sel(ect)-Merge. In Akan, tense is evaluated by Agree and aspect by Selection. The -à morpheme that appears on the non-initial verbs in these clauses is the phonological realization of the morphosyntactic feature bundle [−prog, −fut]. Tense morphology depicts T-v Agree. The same tense inflection on all the verbs appears on verbs because one T-head parallel-Agrees with all of them. Since a single T-head cannot have different interpretations, it results in the matching restriction.
Keywords: verb constructions; Akan; Tense